RETRACTED: A Study on the Participation of Peasants in Rural Environmental Improvement From the Perspective of Sustainable Development - Lin, Runtian; Ma, Xiaowei; Li, Bizhen; Ye, Xinyu; Chen, Xiaomeng; Liang, Shengkai (Frontiers in Environmental Science, 2022)
Peasants are producers and the direct stakeholders of rural environmental problems, and also the core subject of the comprehensive rural ecological improvement. However, in the current mode of rural environmental governance, the government takes the dominant role, with low participation of peasants. Based on the representative micro-survey data of China, and from the perspective of the psychosocial effects of the peasants’ self-identification, this research made use of instrumental variables and generalized structural equation mode (GSEM) to explore the reason behand this phenomenon. The research shows that, first, at present Chinese peasants have a low degree of self-identification, and self-identification has a remarkable and positive stimulating effect on the participation of peasants in rural ecological improvement; second, heterogeneity analysis shows that self-identification is a stronger incentive for peasant groups with female offspring and rural families with relatively higher incomes in the participation of rural environmental improvement, and is a less remarkable incentive for rural families with relatively low incomes; and third, the mediation model results indicate that social fairness and social capital are important mediating paths with which self-identification influences the participation of peasants in rural environmental improvement, and the exertion of the stimulating effect of self-identification on the participation in rural environmental improvement is inseparable from the coordination and integration of the perception effect of peasants as the behavioral subject in terms of social fairness, and is still more inseparable from the support of corresponding social capital. What we’ve discovered means that the enhancement of self-identification of peasants by strengthening the construction of public cultural services and cultural guidance in rural area is the crucial element to motivate the peasants to participate in rural environmental improvement so as to realize sustainable rural development.